The Development of English Learning Media through Animated Videos for Student Grade IX Maarif Ansoru Al Hasaniyah Junior High School - Mulyani, Nanda; Suhono, Suhono; Pratiwi, Wiwied; Sari, Yeasy Agustina; Rokhmawan, Tristan (International Journal on Advanced Science, Education, and Religion, 2024)
The Lack of utilization of learning media leads to lack of student interest in English lessons This study aims to describe the process of developing English learning media through animated videos and the quality of the results of learning animation video development trials. This research is a development research with the ADDIE model. The subjects involved in this study consisted of 1 material expert, 1 media expert, 3 students for individual trials and 33 students for group trials. The methods used for data collection in this study were interviews, observations, questionnaires and documentation. As for the data analysis method using quantitative descriptive analysis and qualitative descriptive analysis. The process of developing English learning media through animated learning videos for grade 9 students goes through 4 stages, namely analysis, design, development, and implementation. The results of the material expert review showed a percentage result of 100% (very feasible), media experts showed a percentage result of 88% (very feasible), individual tests showed a percentage result of 88.6% (very feasible), and the results of the group test showed a percentage result of 85, 6% (very feasible). Based on this analysis, it can be concluded that the development of English learning media through animated videos for grade 9 students of SMP Maarif Ansoru Al Hasaniyah, Rukti Basuki, Rumbia District, Central Lampung Regency is very feasible to use